Frontiers in broiler chicken welfare: adopting early detection of intestinal integrity loss in broiler welfare assessment protocols - de Jong, Ingrid C.; Kar, Soumya Kanti; Kaspers, Bernd (Frontiers in Veterinary Science, 2025)
Current broiler welfare assessment protocols include indicators of impaired intestinal health, but these are non-specific. Loss of intestinal integrity is considered to be a major welfare consequence for broilers but the absence of specific, early indicators in welfare assessment protocols hampers early detection and treatment. Coccidiosis is one of the major threats to intestinal integrity in broiler chickens and taken as an example. We propose the development of specific biomarkers for detecting early onset of intestinal health deterioration. The genotype and external phenotype of organisms are linked by so-called internal phenotypes which are influenced by environmental conditions. We review the impact of coccidiosis on external and internal phenotypes in chickens. The change from the “homeostatic immune response” toward an inflammatory response to control infections is reflected in the change in feeling of comfort to the feeling of discomfort in broilers, in which the gut-brain axis likely plays a crucial role. With this change, a negative emotional state develops. Two routes of developing biomarkers are proposed that are interconnected. The first route is by enabling ~omics techniques for predominantly invasive biomarkers related to the internal phenotype of the broiler chickens during infection. The second approach involves using sensors and automated systems to monitor behavior, vocalizations, and fecal appearance for early disease detection at flock level. By linking these external indicators to invasive biomarkers, we can develop disease-specific biomarkers that enhance early diagnosis with precision and could add significant value to welfare assessment protocols. Research in this area should be encouraged.